Intelligent type 2 diabetes modelling - Quah, Jerome En Zhe. (2012)
Diabetes mellitus affected an estimated 171 million people in the year 2000. The number of diabetic patients is projected to increase to an alarming figure of 366 million by the year 2030, out of which 90 – 95% of them are expected to be type 2 diabetes mellitus (T2DM) patients.